The Representation of Israel-Hamas Conflict in the American and Chinese News Coverage: A Corpus-assisted Comparative Critical Discourse Analysis - Zhu, Jianbin; Liu, Yuqi (International Journal of Social Sciences and Public Administration, 2024)
This research scrutinizes the divergent portrayals of the Israel-Hamas conflict in The New York Times (NYT) and China Daily (CD), utilizing a corpus-based critical discourse analysis approach that blends topic modeling, keyword and collocation analysis, with discourse-historical analysis (DHA) strategies. The analysis reveals how NYT frames the conflict through the lens of democratic values, human rights, and portrays Israel as a defender in the conflict, emphasizing security and terrorism narratives. In contrast, CD offers a narrative that leans towards state sovereignty, national development, and provides a more neutral or sympathetic portrayal of Hamas, reflecting China’s stance on non-interference and peace. This comprehensive analysis underscores the significant role media plays in shaping public perception and policy regarding international conflicts, highlighting the entanglement of media narratives with national geopolitical agendas. By offering insights into the ideological and geopolitical underpinnings of media representations, this study contributes to the broader discourse on media’s influence in international relations, advocating for enhanced critical media literacy among readers. It opens avenues for future research on media narratives in other geopolitical contexts, emphasizing the importance of understanding media as a tool for both reflecting and constructing political realities.